2000
DOI: 10.1080/08903060050136441
|View full text |Cite
|
Sign up to set email alerts
|

Sorghum-cowpea Intercropping: An Effective Technique Against Runoff and Soil Erosion in the Sahel (Saria, Burkina Faso)

Abstract: In the Central Plateau of Burkina Faso, runo † on bare soil amounts to 40% of annual rainfall and soil losses reach 4 to 8 Mg ha ] 1 a ] 1 , despite slopes of under 3%. Several studies have shown that mulching the soil surface can reduce runo † by over 60%. However, the scarcity of straw and the incompatibility of mulching with mechanical soil preparation have prevented the large-scale adoption of the technique. T he study conducted in Saria village where annual rainfall is 800 mm, set out to evaluate the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 4 publications
2
25
0
2
Order By: Relevance
“…Another advantage of intercropping systems is the more efficient utilization of environmental resources, particularly irradiance (Awal et al, 2006) and soil water (Rodrigo et al, 2005), and-in some cases-reduced damage from pests and diseases (Poveda et al, 2008). In addition, the denser ground coverage by the plants may provide greater protection from soil erosion (Zougmore et al, 2000) and weed invasion (van Mourik et al, 2008). Intercropping also gives greater yield stability between years and among sites (Norman et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of intercropping systems is the more efficient utilization of environmental resources, particularly irradiance (Awal et al, 2006) and soil water (Rodrigo et al, 2005), and-in some cases-reduced damage from pests and diseases (Poveda et al, 2008). In addition, the denser ground coverage by the plants may provide greater protection from soil erosion (Zougmore et al, 2000) and weed invasion (van Mourik et al, 2008). Intercropping also gives greater yield stability between years and among sites (Norman et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Zougmore et al (2000) found that sorghum + cowpea intercropping reduced run off by 20-30 % and 45-55 % compared to sole sorghum and sole cowpea, respectively. An increase in soil organic carbon content, available N and P was noticed when cowpea was intercropped with Napier grass under sandy loam conditions of Karnataka (Shekara et al, 2009b).…”
Section: Effect On Plant Growth and Developmentmentioning
confidence: 99%
“…Res. St. (Middle Egypt) during two seasons of 2011/2012and 2012/2013 is located 300 km far south of Cairo the capital. Climate in this region is dry hot in summer with max.…”
Section: Methodsmentioning
confidence: 99%
“…Zougmore et al (2000) showed that sorghum + cowpea intercrops reduced weeds by 20-30 % compared to solid. Abou-Keriasha et al (2011) found that intercropping cowpea on maize and sorghum reduced weed biomass by 77 and 86% compared with solid plots, respectively.…”
mentioning
confidence: 99%